2012
DOI: 10.1002/jbm.b.32707
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of magnesium alloys developed for bioabsorbable orthopedic implants: A general review

Abstract: As a bioabsorbable metal with mechanical properties close to bone, pure magnesium or its alloys have great potential to be developed as medical implants for clinical applications. However, great efforts should be made to avoid its fast degradation in vivo for orthopedic applications when used for fracture fixation. Therefore, how to decease degradation rate of pure magnesium or its alloys is one of the focuses in Research and Development (R&D) of medical implants. It has been recognized that surface modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
132
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(134 citation statements)
references
References 68 publications
0
132
0
2
Order By: Relevance
“…Plasma electrolytic oxidation (PEO) consists of an electrochemical treatment resulting in the production of a more stable ceramic oxide layer in comparison with anodic oxidation (6,(9)(10)(11)(12). As the name suggests, the PEO process is based on a local oxidation of a metal substrate.…”
Section: (Peo) Is An Established Electrochemical Treatment Technique mentioning
confidence: 99%
“…Plasma electrolytic oxidation (PEO) consists of an electrochemical treatment resulting in the production of a more stable ceramic oxide layer in comparison with anodic oxidation (6,(9)(10)(11)(12). As the name suggests, the PEO process is based on a local oxidation of a metal substrate.…”
Section: (Peo) Is An Established Electrochemical Treatment Technique mentioning
confidence: 99%
“…11,12 The corrosion rate of a magnesium implant that is too fast is thus undesirable because both corrosion products have adverse effects on the biocompatibility by negatively influencing the tissue adherence and healing. 21 In the alkaline solutions, surface corrosion products may form, but these products are broken down in the presence of Cl -anions in the SPS:…”
Section: Corrosion Behaviormentioning
confidence: 99%
“…As discussed above, both chemical surface modification methods can obviously enhance the corrosion resistance and reduce the corrosion rate. Our previous study indicated that the pH value of Mg-OH was significantly smaller than that of the pristine magnesium alloy [24] when they were immersed into a corrosion medium for the same time, which contributed to the lower hemolysis rates of the modified samples. However, it was noticeable that the hemolysis rate was larger than 5%, indicating that the modified samples may not be suitable for the blood-contacting biomaterials, although the chemical surface modification can significantly reduce the hemolysis rate.…”
Section: Anticoagulationmentioning
confidence: 94%
“…Among these methods, formation of a chemical conversion layer via chemical surface modification is a simple and cost-effective method and has been increasingly used to improve the corrosion resistance and biocompatibility of magnesium alloy. Generally speaking, chemical surface modification includes alkaline treatment [19], fluoride treatment [20], phosphating [21], anodization [22], ion implantation [23], etc., all of which are associated with the replacement of the natively forming, and not particularly the corrosion resistant oxide layer on the surface of the Mg substrate [24]. By chemical surface modification, a dense and stable chemical conversion layer can be produced on the magnesium alloys.…”
Section: Introductionmentioning
confidence: 99%